Some Charasteristics of Teaching History in Special Educational Institutions - Lipeyko, V. F.; Maslovska, Yu. S.; Chuvpylo, R. I.; Chuvpylo, A. A. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the psychological characteristics of teaching history in special educational institutions and the training of future graduates for admission to higher education institutions. The actuality of the research related to the process of improving teaching methods in high school. Both general (analysis, synthesis, deduction, induction, specification) and special pedagogical, neuropsychological and educational methods are used. As a result of study the neuropsychological properties of assimilation of information by teenagers and dependent of learning process on neurophysiology are analyzed. The properties of memory, methods of its training and improvement are shown. It is recommended to pay attention to the development of the emotional center of the brain that is directly related to long-term memory. The authors distinguish a number of factors that contribute to the development of memory, offering didactic methods of training. The role of extracurricular activities in the increasing interest in the subject and expanding world of students is considered. The practices of stimulation mental processes, educational games, contests, drawings, application of classical music, holding events during the history teaching are shown. The authors conclude that only comprehensive application of pedagogical and psychological methods, taking into account the individual child can bring results.